1993
DOI: 10.1346/ccmn.1993.0410312
|View full text |Cite
|
Sign up to set email alerts
|

Swelling Properties of Microbially Reduced Ferruginous Smectite

Abstract: Abstract--Structural Ire in ferruginous smectite (sample SWa-1, Source Clays Repository of the Clay Minerals Society) was reduced by a mixture of five Pseudomonas species of bacteria in a defined Fe-free medium to determine the effect of microbial reduction on clay swelling. Iron(II), total Fe, and gravimetric water content (row/too) were determined in clay gels equilibrated at applied pressures of 0.1, 0.3, and 0.5 MPa. The water content of microbially reduced SWa-1 decreased at all three applied pressures as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 21 publications
4
46
0
Order By: Relevance
“…(Yan and Stucki, 1999). The reduction of structural Fe also increases the surface-charge density of the clay (Stucki, 1988;Stucki and Tessier, 1991;Gates et al, 1993;Yan and Stucki, 1999), causing the Fe(II)-bearing smectites to acquire a strong nucleophilic character that facilitates the transformation of chlorinated alkanes. The high concentration of H20 relative to that of 5CA, and the fact that smectite surfaces hydrate (Yan et al, 10 ...... 1996b, 1996cYan and Stucki, 1999), suggest that H20 molecules mediate the hydrogen bridging and the long-range interactions between 5CA and the clay surface ("outer sphere complex"; Wilkins, 1991).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Yan and Stucki, 1999). The reduction of structural Fe also increases the surface-charge density of the clay (Stucki, 1988;Stucki and Tessier, 1991;Gates et al, 1993;Yan and Stucki, 1999), causing the Fe(II)-bearing smectites to acquire a strong nucleophilic character that facilitates the transformation of chlorinated alkanes. The high concentration of H20 relative to that of 5CA, and the fact that smectite surfaces hydrate (Yan et al, 10 ...... 1996b, 1996cYan and Stucki, 1999), suggest that H20 molecules mediate the hydrogen bridging and the long-range interactions between 5CA and the clay surface ("outer sphere complex"; Wilkins, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…The solute molecules experience short-and long-range interactions at the clay-water interface (Zhang et al, 1990;Stucki and Tessier, 1991;Barriuso et al, 1994;Xu, 1998) that may lead to the transformation of organic compounds (Cervini-Silva et al, unpubl, data). The oxidation state of structural Fe in smectite clays is known to exert a profound influence on surface chemical properties of clays (Stucki, 1997), particularly as they relate to hydration (Stucki et al, 1984;Gates et aL, 1993;Yah and Stucki, 1999), but evidence is emerging that these effects extend also to organic herbicides (Xu, 1998). Initial studies further indicate that the acid-base reactivity of smectites towards pentachloroethane (5CA) changes during the reduction of structural Fe (CerviniSilva et al, unpubl, data).…”
Section: Introductionmentioning
confidence: 99%
“…This suspension was divided equally among five cells of a miniature swelling-pressure apparatus (Stucki et al, 1984a;Gates et al, 1993) by inserting two septum-penetration needles into the suspension. Through one needle, O2-free N2 gas was applied to pressurize the tube, forcing the suspension out through the other needle into the swelling-pressure cell via an open ball valve at its top.…”
Section: Clay Dehydration At Varying Swelling Pressure 1i (Drying Cumentioning
confidence: 99%
“…The oxidation state of structural Fe in smectite has a profound effect on the chemical and physical behavior of the smectite (Stucki, 1988), but relatively little is known about the underlying mechanisms for these effects. Results by Stucki and co-workers (Gates et aI., 1993;Lear and Stucki, 1989;Stucki et al, 1984a) revealed that the reduction of structural Fe(III) to Fe(II) in the octahedral sheet of smectite greatly decreases swelling in water, whether reduced by sodium dithionite (Stucki et al, 1984a) or by bacteria (Gates et al, 1993;Kostka et al, 1999). Stucki et al (1984a) attributed differences in swellability of oxidized and reduced clays to the collapse of clay interlayers as a result of Fe reduction, which removed a portion of the structure from the swelling component of the system.…”
Section: Introductionmentioning
confidence: 99%
“…The dominant octahedral cation in nontronites and ferruginous smectite is Fe; and in some nontronites Fe occupies a fraction of the tetrahedral sites (Goodman et al 1976, Cardile 1987, 1989, Cardile and Johnston 1985, 1986, Luca 1991, Luca and Cardile 1989. It is the only major element in the smectite structure that potentially may exist in two relatively stable oxidation states, Fe(II) and Fe(III), and a change in its oxidation state in situ alters the physical and chemical properties of the clay (Stucki 1988, and references therein, Komade1 et al 1990, Stucki and Tessier 1991, Khaled and Stucki 1991, Gates et al 1993.…”
Section: Introductionmentioning
confidence: 99%